Restitution rights for children of victims of sexual crimes: between protection and reresting - Siti Hudzaifah Miftahul Jannah; Syamsuddin Muchtar; Hijrah Adhyanti Mirzana (University of Merdeka Malang, 2021)
One of the crimes that are prone to happen to children is sexual crime. Sexual crimes committed against children will have a psychological impact on the child, in the form of mental and emotional state disorders, so that the child who is the victim should be given great attention to the suffering or loss experienced in the form of restitution from the perpetrator. The purpose of this research is to study and analyze how the fulfillment of restitution for child victims of sexual crimes and the extent to which law enforcers and victims influence the fulfillment of these restitution rights, so that empirical research methods are used to answer these problems. The results of this study indicate that the fulfillment of restitution rights for child victims of sexual crimes in the city of Makassar is not fulfilled. This is evidenced by only one case where the victim submitted a request for restitution and the victim did not get restitution from the perpetrator. Law enforcers and victims each have influence in fulfilling restitution rights. Even so, the role of the victim has a bigger influence, this is because even though the law enforcer should inform the victim about the right of restitution, it is the victim who decides whether to apply for restitution or not because restitution can only be obtained if the victim submits a request. not automatically accepted by the victim.How to cite item: Miftahul Jannah, S., Muchtar, S., Mirzana, H. (2021). Restitution rights for children of victims of sexual crimes: between protection and reresting. Jurnal Cakrawala Hukum, 12(2), 223-232. doi:https://doi.org/10.26905/idjch.v12i2.4705